Nickel-copper bimetallic nano-catalyst as well as preparation method and application thereof

By uniformly dispersing nickel-copper metal particles on multi-layer nitrogen-doped graphene, using the interaction between nano-wrinkle structure and metal atoms, the problem of low efficiency of existing catalysts is solved, and efficient carbon dioxide electroreduction and carbon monoxide selectivity is achieved. The stability and Faraday efficiency of the catalyst are significantly improved.

CN119162583APending Publication Date: 2024-12-20ZHEJIANG WANLI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311167213.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing carbon dioxide electroreduction catalyst reduction products have low efficiency and low selectivity, making them difficult to meet production and use needs.

Method used

Using nickel-copper bimetallic nanocatalyst, by uniformly dispersing nickel-metal particles and copper metal particles on multi-layer nitrogen-doped graphene, the interaction between nanowrinkle structure and metal atoms is used to generate carbon monoxide and inhibit the formation of hydrogen, thereby improving the Catalytic efficiency of carbon dioxide electroreduction.

Benefits of technology

It significantly improves the catalytic efficiency of carbon dioxide electroreduction, improves the selectivity and stability of the catalyst, extends the life of the catalyst, and maintains high Faraday efficiency and carbon monoxide selectivity within a wide potential window.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162583A_ABST
    Figure CN119162583A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-copper bimetallic nano-catalyst and a preparation method and application thereof.The nickel-copper bimetallic nano-catalyst comprises multilayer nitrogen-doped graphene, nickel metal particles and copper metal particles, and the multilayer nitrogen-doped graphene is provided with a plurality of wrinkle structures; the nickel metal particles and the copper metal particles are distributed on the surface and inside the multi-layer nitrogen-doped graphene. According to the catalyst, nickel metal particles and copper metal particles are uniformly dispersed on multi-layer nitrogen-doped graphene through a nano wrinkle structure, and the atomic-scale dispersed nickel-copper bimetallic nano-catalyst can generate carbon monoxide with high selectivity and effectively inhibit generation of hydrogen; the problem that the selectivity of reduction products of an existing copper-based catalyst is not high is solved, and the catalytic efficiency of carbon dioxide electroreduction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal catalysts, and in particular to a nickel-copper bimetallic nanocatalyst and a preparation method and application thereof. Background Art

[0002] In recent years, the problem of global warming has become increasingly serious. Global warming is mainly caused by the greenhouse effect, which is mainly caused by excessive emissions of carbon dioxide. With the increasing attention paid by countries around the world to carbon emissions and the introduction of concepts such as "carbon peak" and "carbon neutrality", the world's attention to converting greenhouse gases, mainly carbon dioxide, into value-added products is increasing. Carbon dioxide electroreduction is currently a commonly used method for carbon dioxide treatment, but the Faraday efficiency of the reduction product of the existing carbon dioxide electroreduction catalyst is too low and the current density is too small to meet the needs of production and use.

[0003] Among the numerous carbon dioxide electroreduction catalysts, copper-based materials are one of the most promising non-precious metals in carbon dioxide electroreduction because their products have the advantage of close to 100% Faraday efficiency. However, copper-based materials still have problems such as low selectivity of reduction products, narrow potential window required for reaction, and large overpotential, which reduce their catalytic efficiency for carbon dioxide reduction. Summary of the invention

[0004] The present invention provides a nickel-copper bimetallic nanocatalyst, which uniformly disperses nickel metal particles and copper metal particles on multilayer nitrogen-doped graphene through a nano-wrinkle structure. The atomically dispersed nickel-copper bimetallic nanocatalyst can generate carbon monoxide with high selectivity and effectively inhibit the generation of hydrogen, thereby solving the problem of low selectivity of reduction products of existing copper-based catalysts and improving the catalytic efficiency of carbon dioxide electroreduction.

[0005] In order to solve the above technical problems, the present invention provides a nickel-copper bimetallic nanocatalyst, comprising: multilayer nitrogen-doped graphene, nickel metal particles, and copper metal particles, wherein the multilayer nitrogen-doped graphene has a plurality of nano-wrinkle structures, and the nickel metal particles and the copper metal particles are distributed on the surface and inside of the multilayer nitrogen-doped graphene.

[0006] In this case, nickel metal particles and copper metal particles are evenly distributed on the surface of multilayer nitrogen-doped graphene and its nano-wrinkle structure. At the same time, the interior of the multilayer nitrogen-doped graphene also contains some nickel metal particles and copper metal particles. The interaction between the nickel metal particles and the copper metal particles can effectively improve the overall rate of the interfacial catalytic process.

[0007] In a preferred or optional embodiment, the nickel metal particles and the copper metal particles exist in the form of a bimetallic pair, and the nickel metal particles and the copper metal particles are coupled and connected.

[0008] In a preferred or alternative embodiment, the distance between the nickel metal particles and the copper metal particles is 0.2 nm to 0.5 nm.

[0009] In a preferred or optional embodiment, the nickel metal particles and the copper metal particles exist in the form of bimetallic clusters, and the bimetallic clusters are distributed on the nano-wrinkle structure.

[0010] The present invention also provides a method for preparing a nickel-copper bimetallic nanocatalyst, which is used to prepare the catalyst, comprising:

[0011] S100: mixing dicyandiamide, glucose and deionized water in a mass ratio of (18-22): (0.9-1.1): (200-210) to obtain a first mixture;

[0012] S200: adding copper chloride dihydrate and nickel chloride in a ratio of (0.9-1.1):(1-2) to the first mixed material to obtain a second mixed material;

[0013] S300: heating the second mixed material to 75° C. to 85° C. and keeping the temperature until the liquid in the second mixed material is completely evaporated, and grinding to obtain a precursor powder;

[0014] S400: placing the precursor powder in a reactor and sintering at high temperature to obtain a nickel-copper bimetallic nanocatalyst.

[0015] In this case, a mixture of dicyandiamide and glucose was calcined at high temperature to generate multilayer nitrogen-doped graphene. At the same time, the nano-wrinkle structure on the multilayer nitrogen-doped graphene was used to effectively disperse the nickel and copper particles, preventing the metal particles from agglomerating to form nanoparticles, thereby effectively generating atomically dispersed nickel-copper bimetallic nanocatalysts.

[0016] In a preferred or optional embodiment, in S200, added to the first mixture are a cupric chloride dihydrate solution with a concentration of 8 mol / L to 13 mol / L and a nickel chloride solution with a concentration of 12 mol / L to 17 mol / L in a volume ratio of 1: (0.9 to 1.1).

[0017] In a preferred or optional embodiment, the mass ratio of dicyandiamide to nickel chloride contained in the second mixed material is (4.5-5.5):(1.6-2.2).

[0018] In a preferred or optional embodiment, in S400, the high temperature sintering is to heat the precursor powder to 890°C to 910°C at a heating rate of 2°C / min to 4°C / min, and keep the temperature for 100min to 150min.

[0019] The present invention also provides an application of the nickel-copper bimetallic nanocatalyst for carbon dioxide electro-reduction catalysis.

[0020] In a preferred or optional embodiment, within a wide potential window range of -0.74 V (vs. RHE) to -1.14 V (vs. RHE), the Faradaic efficiency of the nickel-copper bimetallic nanocatalyst is greater than 90%, and the carbon monoxide selectivity of the nickel-copper bimetallic nanocatalyst is greater than 90%.

[0021] In summary, the present invention has the following beneficial effects:

[0022] (1) The nickel-copper bimetallic nanocatalyst of the present invention utilizes the interaction between nickel and copper metal atoms to improve the overall rate of the interfacial catalytic process. The nickel-copper bimetallic nanocatalyst of the present invention exhibits extremely high catalytic selectivity and stability at the optimal potential, and can effectively improve the catalytic efficiency of carbon dioxide electrocatalysis;

[0023] (2) The multilayer nitrogen-doped graphene of the nickel-copper bimetallic nanocatalyst of the present invention has many local nano-wrinkle structures, which are conducive to the anchoring and dispersion of metal species, and are not easy to make metal particles agglomerate to form nanoparticles, thereby enhancing the overall stability of the catalyst and extending the life of the catalyst;

[0024] (3) The nickel-copper bimetallic nanocatalyst of the present invention significantly improves the overpotential in the carbon dioxide reduction process through the nano-wrinkle structure of graphene and the interaction between the two metal atoms, and enhances the overall stability of the catalyst. At the same time, it also significantly improves the selectivity and Faraday efficiency of carbon monoxide.

[0025] (4) The nickel-copper bimetallic nanocatalyst of the present invention has two forms: bimetallic pairs and bimetallic clusters. The current densities of the two are different. According to the actual application scenario, a catalyst of a suitable form can be selected to obtain a corresponding current density.

[0026] (5) The present invention uses dicyandiamide as a sacrificial template to synthesize atomically dispersed nickel-copper bimetallic nanocatalysts. The synthesis method is simple, highly operable, and can achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of a sample prepared in Example 1 provided by the present invention;

[0028] Figure 2 A transmission electron microscope image of a sample prepared in Example 1 provided by the present invention;

[0029] Figure 3The element distribution diagram of the sample prepared in Example 1 provided by the present invention;

[0030] Figure 4 This is a scanning electron microscope image of a sample prepared in Example 4 provided by the present invention;

[0031] Figure 5 A transmission electron microscope image of a sample prepared in Example 4 provided by the present invention;

[0032] Figure 6 The element distribution diagram of the sample prepared in Example 4 provided by the present invention;

[0033] Figure 7 A Faraday efficiency diagram of a sample prepared in Example 1 provided by the present invention;

[0034] Figure 8 The Faraday efficiency diagram of the sample prepared in Example 4 provided by the present invention;

[0035] Fig. 9 A comparison chart of carbon monoxide selectivity of samples prepared in Example 1 and Example 4 provided by the present invention;

[0036] Fig.10 A comparison chart of the carbon monoxide current density of the samples prepared in Example 1 and Example 4 provided by the present invention. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0038] Embodiment 1:

[0039] This embodiment provides a method for preparing a nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair, and the specific preparation steps are as follows:

[0040] S100: dissolving 5.0 g of dicyandiamide and 0.25 g of glucose in 200 mL of deionized water to obtain a first mixture;

[0041] S200: 1 mL of a solution containing 0.0125 mol of cupric chloride dihydrate and 0.0125 mol of nickel chloride was added dropwise to the first mixed material, and the mixture was stirred at a speed of 1000 rpm using a magnetic stirrer to mix evenly to obtain a second mixed material;

[0042] S300: heating and stirring the second mixed material, maintaining the temperature at 80° C. until the liquid is completely evaporated, and grinding the obtained solid into powder to obtain a precursor powder;

[0043] S400: The precursor powder is placed in a crucible with a lid, and the crucible is placed in a tube furnace and heated to 900°C at a rate of 3°C / min and maintained at 900°C for two hours, during which argon gas is continuously introduced. After the heating process is completed, the temperature is cooled to room temperature in an argon environment and then taken out to obtain a nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair.

[0044] Embodiment 2:

[0045] This embodiment provides a method for preparing a nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair, and the specific preparation steps are as follows:

[0046] S100: dissolving 5.0 g of dicyandiamide and 0.25 g of glucose in 200 mL of deionized water to obtain a first mixture;

[0047] S200: 1 mL of a solution containing 0.0127 mol of copper chloride dihydrate and 0.0123 mol of nickel chloride was added dropwise to the first mixed material, and the mixture was stirred at a speed of 1000 rpm using a magnetic stirrer to mix evenly to obtain a second mixed material;

[0048] S300: heating and stirring the second mixed material, maintaining the temperature at 75° C. until the liquid is completely evaporated, and grinding the obtained solid into powder to obtain a precursor powder;

[0049] S400: The precursor powder is placed in a crucible with a lid, and the crucible is placed in a tube furnace and heated to 890°C at a rate of 2°C / min and maintained at 890°C for two hours, during which argon gas is continuously introduced. After the heating process is completed, the temperature is cooled to room temperature in an argon environment and then taken out to obtain a nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair.

[0050] Embodiment three:

[0051] This embodiment provides a method for preparing a nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair, and the specific preparation steps are as follows:

[0052] S100: dissolving 5.0 g of dicyandiamide and 0.25 g of glucose in 200 mL of deionized water to obtain a first mixture;

[0053] S200: 1 mL of a solution containing 0.011 mol of cupric chloride dihydrate and 0.0135 mol of nickel chloride was added dropwise to the first mixed material, and the mixture was stirred at a speed of 1000 rpm using a magnetic stirrer to mix evenly to obtain a second mixed material;

[0054] S300: heating and stirring the second mixed material, maintaining the temperature at 85° C. until the liquid is completely evaporated, and grinding the obtained solid into powder to obtain a precursor powder;

[0055] S400: The precursor powder is placed in a crucible with a lid, and the crucible is placed in a tube furnace and heated to 910°C at a rate of 4°C / min and maintained at 910°C for two hours, during which argon gas is continuously introduced. After the heating process is completed, the temperature is cooled to room temperature in an argon environment and then taken out to obtain a nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair.

[0056] Embodiment 4:

[0057] This embodiment provides a method for preparing a nickel-copper bimetallic nanocatalyst in the form of a bimetallic cluster, and the specific preparation steps are as follows:

[0058] S100: dissolving 5.0 g of dicyandiamide and 0.25 g of glucose in 200 mL of deionized water to obtain a first mixture;

[0059] S200: 1 mL of a solution containing 0.0083 mol of copper chloride dihydrate and 0.0167 mol of nickel chloride was added dropwise to the first mixed material, and the mixture was stirred at a speed of 1000 rpm using a magnetic stirrer to mix evenly to obtain a second mixed material;

[0060] S300: heating and stirring the second mixed material, maintaining the temperature at 80° C. until the liquid is completely evaporated, and grinding the obtained solid into powder to obtain a precursor powder;

[0061] S400: The precursor powder is placed in a crucible with a lid, and the crucible is placed in a tube furnace and heated to 900°C at a rate of 3°C / min and maintained at 900°C for two hours, during which argon gas is continuously introduced. After the heating process is completed, the temperature is cooled to room temperature in an argon environment and then taken out to obtain a nickel-copper bimetallic nanocatalyst in the form of a bimetallic cluster.

[0062] Embodiment five:

[0063] This embodiment provides a method for preparing a nickel-copper bimetallic nanocatalyst in the form of a bimetallic cluster, and the specific preparation steps are as follows:

[0064] S100: dissolving 5.0 g of dicyandiamide and 0.25 g of glucose in 200 mL of deionized water to obtain a first mixture;

[0065] S200: 1 mL of a solution containing 0.0092 mol of copper chloride dihydrate and 0.0169 mol of nickel chloride was added dropwise to the first mixed material, and the mixture was stirred at a speed of 1000 rpm using a magnetic stirrer to mix evenly to obtain a second mixed material;

[0066] S300: heating and stirring the second mixed material, maintaining the temperature at 75° C. until the liquid is completely evaporated, and grinding the obtained solid into powder to obtain a precursor powder;

[0067] S400: The precursor powder is placed in a crucible with a lid, and the crucible is placed in a tube furnace and heated to 895°C at a rate of 2.5°C / min and maintained at 895°C for two hours, during which argon gas is continuously introduced. After the heating process is completed, the temperature is cooled to room temperature in an argon environment and then taken out to obtain a nickel-copper bimetallic nanocatalyst in the form of a bimetallic cluster.

[0068] Embodiment six:

[0069] This embodiment provides a method for preparing a nickel-copper bimetallic nanocatalyst in the form of a bimetallic cluster, and the specific preparation steps are as follows:

[0070] S100: dissolving 5.0 g of dicyandiamide and 0.25 g of glucose in 200 mL of deionized water to obtain a first mixture;

[0071] S200: 1 mL of a solution containing 0.0081 mol of cupric chloride dihydrate and 0.0165 mol of nickel chloride was added dropwise to the first mixed material, and the mixture was stirred at a speed of 1000 rpm using a magnetic stirrer to mix evenly to obtain a second mixed material;

[0072] S300: heating and stirring the second mixed material, maintaining the temperature at 85° C. until the liquid is completely evaporated, and grinding the obtained solid into powder to obtain a precursor powder;

[0073] S400: The precursor powder is placed in a crucible with a lid, and the crucible is placed in a tube furnace and heated to 905°C at a rate of 3.5°C / min and maintained at 905°C for two hours, during which argon gas is continuously introduced. After the heating process is completed, the temperature is cooled to room temperature in an argon environment and then taken out to obtain a nickel-copper bimetallic nanocatalyst in the form of a bimetallic cluster.

[0074] Performance Test:

[0075] The two different forms of nickel-copper bimetallic nanocatalysts prepared in Example 1 and Example 4 were subjected to scanning electron microscopy, transmission electron microscopy, and element distribution detection, respectively. The detection results are as follows: Figure 1-6 shown.

[0076] like Figure 1 As shown in the figure, many nano-wrinkle structures are formed on the graphene substrate of the nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair, which is conducive to the anchoring and dispersion of metal species. Figure 2 As shown in the figure, a large number of bimetallic pairs with a distance between 0.2nm and 0.5nm are formed on the graphene substrate of the nickel-copper bimetallic nanocatalyst in the form of bimetallic pairs, and no metal nanoparticles are formed, indicating that there is a strong electronic interaction between the two atoms, proving the coupling between Ni atoms and Cu atoms. Figure 3As shown, the two metal elements nickel and copper in the nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair are evenly distributed on the entire graphene substrate.

[0077] like Figure 4 As shown in the figure, many nano-wrinkle structures are also formed on the graphene substrate of the Ni-Cu bimetallic nanocatalyst in the form of bimetallic clusters, which is conducive to the anchoring and dispersion of metal species. Figure 5 As shown in Figure 2, the Ni-Cu bimetallic nanocatalyst in the form of bimetallic clusters formed a large number of highly dispersed atomic clusters on the nanowrinkle structure. Figure 6 As shown in Figure 2, the nickel and copper bimetallic nanocatalysts in the form of bimetallic clusters are uniformly distributed on the entire graphene substrate and are Figure 3 Compared with the above, it can be seen that the distribution of copper element in the nickel-copper bimetallic nanocatalyst in the form of bimetallic clusters is obviously more sparse, and the distribution of nickel element is obviously more dense.

[0078] The two different forms of nickel-copper bimetallic nanocatalysts prepared in Example 1 and Example 4 were tested for Faraday efficiency, carbon monoxide selectivity, and carbon monoxide current density. The test results are as follows: Figure 7-10 The Faraday efficiency test was performed in an H-cell with 0.5 M potassium bicarbonate as the electrolyte.

[0079] like Figure 7 As shown in the figure, the bimetallic pair-shaped nickel-copper bimetallic nanocatalyst can generate carbon monoxide with high selectivity and effectively inhibit the generation of hydrogen. It exhibits a Faraday efficiency of more than 95% in a wide potential window range of -0.74V (vs.RHE) to -1.14V (vs.RHE). At a potential of -0.94V (vs.RHE), the carbon monoxide Faraday efficiency of the catalyst reaches a peak of 99%. Figure 8 As shown, the bimetallic cluster-shaped nickel-copper bimetallic nanocatalyst can generate carbon monoxide with high selectivity and effectively inhibit the generation of hydrogen, showing a Faraday efficiency of more than 90% in a wide potential window range of -0.74V (vs.RHE) to -1.14V (vs.RHE). At a potential of -0.74V (vs.RHE), the carbon monoxide Faraday efficiency of the catalyst reaches a peak of 95%.

[0080] like Fig. 9 As shown, both forms of nickel-copper bimetallic nanocatalysts can generate carbon monoxide with high selectivity and maintain the selectivity of carbon monoxide above 90% in a wide potential window. Among them, the carbon monoxide Faraday efficiency of the nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair reaches a peak of 99% at a potential of -0.94 V (vs. RHE).

[0081] like Fig.10 As shown in the figure, both forms of nickel-copper bimetallic nanocatalysts can generate carbon monoxide at a high current density. The carbon monoxide partial current density of the nickel-copper bimetallic nanocatalyst in the form of a bimetallic pair reaches a maximum at a potential of -1.14 V (vs. RHE), reaching 62.04 mA / cm 2 , slightly higher than the 42.36 mA / cm reached by the Ni-Cu bimetallic nanocatalyst in the form of bimetallic clusters at this potential. 2 .

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nickel-copper bimetallic nanocatalyst, characterized in that: include: Multilayer nitrogen-doped graphene, nickel metal particles, and copper metal particles. The multilayer nitrogen-doped graphene has a plurality of nano-wrinkle structures. The nickel metal particles and the copper metal particles are distributed on the surface and inside of the multilayer nitrogen-doped graphene.

2. The nickel-copper bimetallic nanocatalyst according to claim 1, characterized in that: The nickel metal particles and the copper metal particles exist in the form of a bimetallic pair, and the nickel metal particles and the copper metal particles are coupled and connected.

3. The nickel-copper bimetallic nanocatalyst according to claim 2, characterized in that: The distance between the nickel metal particles and the copper metal particles is 0.2 nm to 0.5 nm.

4. The nickel-copper bimetallic nanocatalyst according to claim 1, characterized in that: The nickel metal particles and the copper metal particles exist in the form of bimetallic clusters, and the bimetallic clusters are distributed on the nano-wrinkle structure.

5. A method for preparing a nickel-copper bimetallic nanocatalyst, characterized in that: The method for preparing the nickel-copper bimetallic nanocatalyst according to any one of claims 1 to 4 comprises: S100: mixing dicyandiamide, glucose and deionized water in a mass ratio of (18-22): (0.9-1.1): (200-210) to obtain a first mixture; S200: adding copper chloride dihydrate and nickel chloride in a ratio of (0.9-1.1):(1-2) to the first mixed material to obtain a second mixed material; S300: heating the second mixed material to 75° C. to 85° C. and keeping the temperature until the liquid in the second mixed material is completely evaporated, and grinding to obtain a precursor powder; S400: placing the precursor powder in a reaction kettle and sintering at high temperature to obtain the nickel-copper bimetallic nanocatalyst.

6. The preparation method according to claim 5, characterized in that: In S200, a cupric chloride dihydrate solution with a concentration of 8 mol / L to 13 mol / L and a nickel chloride solution with a concentration of 12 mol / L to 17 mol / L in a volume ratio of 1:(0.9 to 1.1) are added to the first mixture.

7. The preparation method according to claim 6, characterized in that: The mass ratio of dicyandiamide to nickel chloride contained in the second mixture is (4.5-5.5):(1.6-2.2).

8. The preparation method according to claim 5, characterized in that: In the S400 , the high temperature sintering is to heat the precursor powder to 890° C. to 910° C. at a heating rate of 2° C. / min to 4° C. / min, and keep the temperature for 100 min to 150 min.

9. An application of the nickel-copper bimetallic nanocatalyst as claimed in any one of claims 1 to 4, characterized in that: Used in carbon dioxide electroreduction catalysis.

10. The use of the nickel-copper bimetallic nanocatalyst according to claim 9, characterized in that: In a wide potential window range of -0.74 V (vs. RHE) to -1.14 V (vs. RHE), the Faraday efficiency of the nickel-copper bimetallic nanocatalyst is greater than 90%, and the carbon monoxide selectivity of the nickel-copper bimetallic nanocatalyst is greater than 90%.

Citation Information

Cited By

  • Multilayer electrocatalyst for the conversion of CO2 to ethylene glycol

    DE102025101283A1